2011
DOI: 10.1186/1471-230x-11-14
|View full text |Cite
|
Sign up to set email alerts
|

The actin-bundling protein Fascin is overexpressed in inflammatory bowel disease and may be important in tissue repair

Abstract: BackgroundFascin is associated with increased cell motility in colorectal tumours but is absent from the normal colonic epithelium. We examined the expression of fascin in inflammatory bowel disease (IBD) and its location at regions undergoing restitution and regeneration. Tissue repair is essential for disease remission and we sought to determine the effects of therapeutic modalities on fascin expression and function using an in vitro model.MethodsImmunohistochemistry was performed on colonic tissue from IBD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Rifaximin-mediated reduction of RbAp48 further suggested that cytoprotection was likely due do modifications to the expression levels of proteins associated with the cytoskeleton and cellular integrity. This observation is further supported by the observation that fascin, an organizational protein that bundles actin in cells [38] and highly expressed in colorectal adenocarcinomas and in patients with inflammatory bowel disease [3], [38] was up-regulated following rifaximin treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Rifaximin-mediated reduction of RbAp48 further suggested that cytoprotection was likely due do modifications to the expression levels of proteins associated with the cytoskeleton and cellular integrity. This observation is further supported by the observation that fascin, an organizational protein that bundles actin in cells [38] and highly expressed in colorectal adenocarcinomas and in patients with inflammatory bowel disease [3], [38] was up-regulated following rifaximin treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Qualtrough observed a higher Fascin expression in colon tissues among patients with colitis ulcerosa and Leśniowski-Crohn disease [19]. The expression was increased especially in repaired tissues.…”
Section: Discussionmentioning
confidence: 79%
“…The expression was increased especially in repaired tissues. In neoplastic transformation, an increased Fascine expression correlates with poor survival [9,19]. UVB is a well-known factor that inhibits an immune response in dermis changing the antigen presenting cells' function and generating antigen tolerance in CD4+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that chronic inflammation is an environment likely to induce fascin expression. There are several pieces of evidence that support this hypothesis: Fascin is overexpressed in inflammatory bowel disease and the expression correlates with the disease severity . Inflammation‐related cytokines TGF‐β and TNF‐α induce fascin expression .…”
Section: Discussionmentioning
confidence: 97%